2020
DOI: 10.1155/2020/1316796
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Hard Rock Breaking with Fiber Laser: Surface Failure Characteristics and Perforating Mechanism

Abstract: The rock-breaking characteristics and the influence factors of laser perforation are investigated in this study. A series of fiber laser perforation experiments on basalt, sandstone, and granite were conducted. Experimental measurements of rock failure morphologies and composition tests showed that the main surface features are thermal cracks and glazed layer formed by the melting and condensing of rock in laser perforation. It is also found that higher quartz content could help reduce the glazed degree of roc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…And a small amount of bubbles appear in the molten pool, due to the escape of the sealed gases in the original pores and the thermally decomposed gases of special mineral components (such as silicate, etc.) [22]. With the continuous irradiation of the laser, the temperature continues to rise and the molten pool gradually boils; the number of bubbles increases, and the bubbles constantly grow until they burst.…”
Section: Introductionmentioning
confidence: 99%
“…And a small amount of bubbles appear in the molten pool, due to the escape of the sealed gases in the original pores and the thermally decomposed gases of special mineral components (such as silicate, etc.) [22]. With the continuous irradiation of the laser, the temperature continues to rise and the molten pool gradually boils; the number of bubbles increases, and the bubbles constantly grow until they burst.…”
Section: Introductionmentioning
confidence: 99%
“…In order to achieve the efficient and micro-disturbance sampling of unmanned drilling of lunar rock, it is urgent to innovate the drilling method and develop efficient drilling advanced drilling equipment. For this reason, some scholars put forward the idea of jet, microwave [10][11][12] , laser and other new means to assist in mechanical breaking of hard rock, and carried out a series of beneficial research.Laser as a monochromatic and directional high energy density beam is widely used [13,14].Laser rock breaking technology has been widely concerned by scholars due to its attractive prospect of low cost, high efficiency and high reliability, and has become a research hotspot in recent years [15].Yang et al [16]carried out the hard rock breaking experiment with fiber laser and described the evolution process of laser perforation in detailToshio et al [17]studied the mechanism of borehole rupture by fixed and moving lasers.Pan et al [18] studied the influence of laser irradiation parameters on the special fracture characteristics of shale.Chen et al [19] found that the penetration rate of elliptical laser assisted bit drilling is 61% higher than that of conventional non laser drilling.…”
Section: Introductionmentioning
confidence: 99%
“…Buckstegge et al [40] found that the formation of crack and splintering caused by laser irradiation was due to irregular thermal expansion. Yang et al [41,42] experimentally investigated the rock-temperature distribution, specific energy and rate of perforation. They found that the rock-temperature profile strongly depended on the laser power and rock composition.…”
Section: Introductionmentioning
confidence: 99%